THE DRAMATIC APPROACH OF I. HOFFMAN IN STRUCTURING THE SPACE OF FASHION - E. V. Skalatskaya (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of work is to explicate the opportunities of dramatic approach of I. Hoffman to analyse the fashion as a space. A concrete material, where the action of the concept is demonstrated, it is the demonstration of clothing on seasonal fashion shows of designer`s collection. The methodology is the dramatic approach of I. Hoffmann, comparative analysis. The above mentioned methodology allowed us to trace the interconnection of image and fashion in zonal distribution of performance space. Originality consists in enriching of dramatic approach by analysis of fashion space by its zonal distribution that was used in the context of the combination of spatial and image component. Conclusions. Dramatic approach presents new methodology of fashion research that requires further consideration. We can distinguish two levels of understanding the concept of I. Hoffmann: individual and supra-individual, which are combined in spatial terms. I. Hoffmann`s definition of social formation as a space allows you to explore the fashion in this context. Zonal distribution of fashion according to dramatic approach reveals its interconnection with the image. Dramatic approach allows us to trace the dynamics in the space of fashion for disclosure of its ontological characteristics which are associated with space and time. Dualism of separation and unity of zones, their dynamism show the coincidence of image and fashion in spatial level. The proposed general model allows specifying a variety of spaces of fashion in their unity. Spatial differentiation (fashion store, magazine, and showing seasonal collections of designer and other) suggests the possibility of dramatic performance approach in each area, which may be a subject of investigation for the following publication.